Ontogeny of swimming speed, schooling behaviour and jellyfish avoidance by Japanese anchovy Engraulis japonicus - Masuda, R. (Journal of fish biology, 2011)
The ontogeny of swimming speed, schooling behaviour and jellyfish avoidance was studied in hatchery‐reared Japanese anchovy Engraulis japonicus to compare its life‐history strategy with two other common pelagic fishes, jack mackerel Trachurus japonicus and chub mackerel Scomber japonicus. Cruise swimming speed of E. japonicus increased allometrically from 1·4 to 3·9 standard length (LS) per s (LS s−1) from early larval to metamorphosing stage. Burst swimming speed also increased from 6·1 to 28 LS s−1 in these stages. Cruise speed was inferior to that of S. japonicus, as was burst speed to that of T. japonicus. Engraulis japonicus larvae were highly vulnerable to predation by moon jellyfish Aurelia aurita and were readily eaten until they reached 23 mm LS, but not at 26 mm LS. Schooling behaviour (indicated by parallel swimming) started at c. 17 mm LS. Average distance to the nearest neighbour was shorter than values reported in other pelagic fishes. The relatively low predator avoidance capability of E. japonicus may be compensated for by their transparent and thus less conspicuous body, in addition to their early maturation and high fecundity.